Structural and Spectral Analyses of 2-[(2-Benzothiazolylmethyl)thio]-benzenamine and 2-[(2-Benzothiazolylmethyl)thio]-benzenamine hydrobromide - Demoin, Dustin W. (2011)
2-[2-benzothiazoylmethyl)thio]-benzenamine, which was first reported in 1898, was isolated from the reaction of bromoacetyl bromide and 2-aminothiophenol [1]. The product crystallized from an aqueous methanol solution of the reaction mixture to which nickel(II) acetate had been added. 2-[(2-benzothiazolylmethyl)thio]-benzenamine crystallized in the monoclinic system, in space group C2/c, with cell dimensions of a = 27.392 (19) Å, b = 4.730 (3) Å, and c = 23.686 (16) Å, β = 122.465 (6)°, V = 2589(3) Å(3), Z = 8 and refined to R = 0.0343 and R(w) = 0.0844. Crystallization from methanol yielded the product as the hydrobromide salt in the monoclinic space group Cc, with cell dimensions of a = 10.488 (3) Å, b = 33.404 (9) Å, c = 5.2578 (14) Å, β = 116.769(2)°, V = 1644.7(8) Å(3), Z = 4 and refined to R = 0.0296 and R(w) = 0.0600. Mass spectral and NMR analyses confirmed that the bulk and crystalline compound were all 2-[(2-benzothiazolylmethyl)thio]-benzenamine.